Modular irregularity strength of dense graphs - Suparta, I Nengah; Candiasa, Made; Prasancika, Kadek Wahyu; Baca, Martin (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2024)
We solve the open problem posed in Modular irregularity strength of graphs, Electron. J. Graph Theory and Appl. 8 (2020), 435–433, asking about the modular irregularity strength of the complete graph Kn for all n ≥ 3. Furthermore, we establish also the exact values of the modular irregularity strength of complete bipartite graphs Kn, n + t for any positive integer n and t = 0, 1, 2.